Practice in Construction: A Music Therapy Autoethnography in a Decolonial Key - Gracida, Samuel (Voices: A World Forum for Music Therapy, 2025)
This article offers an autoethnographic reflection on decolonial thinking in music therapy. Based on personal experiences as a Mexican music therapist based in Germany (working with displaced persons, collaborating on community projects in Mexico and the Philippines, and participating in international research networks), the author analyzes the ways in which decolonial perspectives in music therapy permeate his music therapy practice. Key contributions from authors who have written about decolonialism, suchas Enrique Dussel, Ramón Grosfoguel, Aníbal Quijano, and Silvia Rivera Cusicanqui, are revisited, as are those from colleagues who have critically addressed coloniality in the field of music therapy, such as the CAMTI Collective. The text proposes a transmodern and pluriversal perspective, recognizing the value of situated knowledge, subjectivity, and intercultural dialogue. It also offers insights into how these terms are used in the author’s experiences and thinking. From this perspective, we are invited to think of decolonization not as an achievable goal, but as an ethical, critical, and constantly evolving practice that requires maintaining a certain degree of discomfort with changing structures of knowledge and practice, recognizing contradictions, and opening spaces for dialogue. Editorial Comment The author has lived in many places and reflects on this in his essay, in which he invites us to move away from dogmatic positions when we encounter the work of colleagues who belong to societies different from our own. As Samuel says, being immersed in colonial systems means that there are dynamics from which we cannot completely escape.” We find his proposal sensitive to the cultural factors of professional practices, but also demanding in terms of the critical thinking and analysis they require.